Rolling‐horizon–based strategy of fully cooperative traffic under signalized intersections. (29th August 2022) - Yao, Yifan; Zhou, Yang; Xia, Jingxin; Wang, Xin; Li, Xiaotian; Ran, Bin
Abstract: Dedicated left‐turn lanes are traditionally used at intersections. This practice may not be optimal where heavy traffic exists from multiple directions. As is well known, the capacity can be increased if vehicles are grouped in the same direction in advance, but the additional infrastructure is usually needed, such as presignal systems. Fortunately, under the development of connected and automated vehicle (CAV) technology, the presignal system can be achieved by coordinating vehicles directly. To this end, we establish a modeling framework and management strategies for pure CAV traffic to achieve direction‐based grouping. A rolling time‐horizon–based sorting strategy is developed to achieve real‐time coordination under uncertain vehicle arrivals. A series of numerical experiments have shown that the improvement of the proposed sorting strategy is significant and robust compared with traditional dedicated left‐turn lane intersections without coordination, especially when the traffic is busy.